Management of Deep Neck Infection Associated with Descending Necrotizing Mediastinitis: A Scoping Review - Bogdan Mihail Cobzeanu; Liliana Moisii; Octavian Dragos Palade; Mihai Ciofu; Florentina Severin; Mihai Dumitru; Luminita Radulescu; Cristian Martu; Mihail Dan Cobzeanu; Geanina Bandol (Medicina, 2025)
Deep neck infection is a pathology at the border of two specialties, otorhinolaryngology and maxillofacial surgery, and represents a medico-surgical emergency. In terms of its evolution, it can extend to the level of the thorax and result in mediastinitis, with difficult evolution and poor prognosis. The aims of this scoping review are to present the etiology, bacteriology, clinical manifestations, and diagnostics, as well as treatment, in light of the research published in the last 5 years on deep neck infection associated with descending necrotizing mediastinitis. The most common primary sources of deep neck infection are odontogenic and tonsillar. The other sources that are involved in deep neck infection are salivary glands, foreign bodies, malignancies, and iatrogenic causes after endoscopic maneuvers. The bacteriologic aspect is polymorphic, including both aerobic and anaerobic species. Complications that may appear include jugular vein thrombosis, airway obstruction, acute respiratory distress syndrome, sepsis, and disseminated intravascular coagulation. Timely diagnosis is important for ensuring the positive evolution of a deep neck infection. A CT scan is important for characterizing the nature of a deep neck lesion and identifying the spaces involved, and this method represents the gold standard for diagnosis of these lesions. Following the establishment of a definitive diagnosis, antibiotic therapy is initiated empirically, and is modified according to bacteriological exam results. The administration of antibiotics is an essential part of the treatment strategy for patients with a deep neck infection. Based on CT results, different surgical methods are applied under general anesthesia. The surgical strategy involves opening and draining the cervical spaces and debriding the necrotic tissue. In the cases of odontogenic causes, drainage and extraction of the infected teeth are performed. It is especially important to follow up on the dynamic progression of the patient. In the management of a deep neck infection associated with descending necrotizing mediastinitis, a multidisciplinary team is necessary.